Septuagint and reception : essays prepared for the Association for the Study of the Septuagint in South Africa - Cook, Johann. (Vetus Testamentum, Supplements, 2009)
A new association for the study of the Septuagint was formed in South Africa recently. The present collection is a compilation of papers delivered at the first conference of this association, as well as other contributions. The volume addresses issues touching on the Septuagint in the broad sense of the word. This includes the Old Greek text (Daniel, Proverbs, Psalms and Lamentations) as well as the reception of the LXX (NT, Augustine and Jerome, et cetera). A few contributions that may be regarded as miscellanea are nevertheless related to matters Septuagintal (Aristeas, Peshitta, Eunochos).